Azulene–boronate esters: colorimetric indicators for fluoride in drinking water. Issue 93 (14th November 2017) - López-Alled, Carlos M.; Sanchez-Fernandez, Adrian; Edler, Karen J.; Sedgwick, Adam C.; Bull, Steven D.; McMullin, Claire L.; Kociok-Köhn, Gabriele; James, Tony D.; Wenk, Jannis; Lewis, Simon E.
Abstract : Sensitive and selective fluoride indicators consisting of a boronate ester receptor motif, conjugated to an azulene reporter motif, are described. These exhibit a colour change visible to the naked eye when exposed to fluoride. Abstract : Low cost and in situ fluoride detection by non-experts is important for the determination of drinking water safety in developing countries. Colour reagents can provide results quickly without expensive equipment, but colorimetric fluoride indicators are often nonspecific, complex to use or do not work in water. Here we show that azulene–boronate indicators respond selectively to fluoride at concentrations relevant to the WHO limit of 1.5 mg L −1 .